Sea Urchin (Echinoidea) Distribution and Abundance in the Intertidal Zone of Bengkayang Regency - Ristanto, Andi; Yanti, Ari Hepi; Setyawati, Tri Rima (Biosaintifika: Journal of Biology & Biology Education, 2018)
Sea urchins is the member of Echinoidea. This species can be found in tropical marine water to the poles. The study aimed to know the types, the abundance and spread of sea urchins in Bengkayang Regency. The research, used the transect method. Each station consisted of 3 transects with a length of 50 meters from the shore into the sea with the distance of 10 meters among the transects. This research obtained five species consisting of three species of the Diadema (genus) and two species of the Echinotrix (genus) i.e. Diadema antillarium, D. savignyi, D. setosum, Echinotrix calamaris and E. deadema. The density of sea urchins in Lemukutan Island ranges from 273 â 453 ind/Ha. The Density of sea urchins on Penata Kecil island ranges from 167 - 347 ind / Ha and on Penata Besar Island has a range from 307 - 387 ind/Ha. The highest diversity of sea urchins was found in Penata Kecil Island of (1.2355). The distribution of sea urchins in Lemukutan and Penata Besar Island was categorized into clumped and evenly distributed, while the distribution of sea urchin on Penata Kecil Island is included in the clustered and random categories. Distribution of sea urchins on the island is influenced by several factors such as sea water waves and food contained in the environment.